Prioritizing Engagement of a Diverse Student Cohort in Online Hydrology Learning at the University of Western Australia - Thompson, Sally E.; Bourke, Sarah A.; Callow, J. Nikolaus; Hipsey, Matthew R. (Frontiers in Education, 2022)
Like most water education institutions worldwide, hydrology instructors at the University of Western Australia (UWA) had to rapidly adapt traditional teaching strategies to manage the Covid-19 pandemic. With diverse student cohorts, including a large fraction of international students prevented from reaching Australia by travel restrictions, key requirements from this transition were to create supportive, inclusive online educational settings, and to maximize student engagement in their courses. Here, we draw on experiences in four hydrology courses to illustrate how we used a holistic approach spanning course structure, content delivery, active learning experiences and authentic assessment to protect these key pedagogical requirements during the transition to online learning. Some aspects of this approach - for example, creating an online `virtual watershed' in lieu of field trips - required sophisticated technology to support online innovation. Other aspects, however, relied primarily on existing features in learning management systems such as Blackboard and on re-organization of course structure and communication approaches to support online learning, with minimal need for new technology or software. The outcomes in these courses as measured by student engagement, enrolment and self-reported satisfaction were positive, with student evaluations remaining similar to those of pre-pandemic levels. Previous interest in running flipped classrooms and familiarity with technology among instructors and students were helpful in enabling the transition. While content-delivery may remain in an online mode for hydrology classes at UWA long term, opportunities to re-introduce field work, laboratories and other face-to-face active learning activities are eagerly awaited by instructors and students alike.